Biasing circuit implementation on DGS for application on 5G mm-Wave SPDT RF switch - Othman, Adib; Majid, H.A.; Al-Fadhali, Najib; Shairi, Noor Azwan; Zakaria, Zahriladha; Jusoh, M (2024)
This paper presents a novel investigation into the integration of DC biasing circuits within single-unit DGS. Two distinct DGS configurations have been examined by using parametric studies to reveal how their unique electromagnetic wave propagation characteristics interact with the biasing circuits. The attenuation response analysis suggests that the dimensions and placement of the biasing circuit structure within the DGS design are critical factors to consider in the future development of electronically switchable DGS. Consequently, it is anticipated that such DGS architectures will be well-suited for integration into 5G mm-wave SPDT RF switches.